Methods of pharmaceutical waste management disposal practiced in sanitation value chain by community pharmacies and households in Nkubu Town (African Journal of Science, Technology and Social Sciences, 2022)
Introduction: Pharmaceutical Waste Management (PWM) has emerged as a challenging issue, with both health and environmental negative impacts. The study assessed the common methods of pharmaceutical waste management disposal in Nkubu town among community pharmacies and households in the sanitation service chain. Problem statement: Increasing disease incidence and prevalence necessitate healthcare practitioners to prescribe and dispense different medications. According to World Health Organization (WHO2010), more than half of all medications are inappropriately prescribed and sold, which causes unnecessary storage in community pharmacies (CPs) and households creating environmental threats that jeopardize efficiency of sanitation service chain.Methods: The study area was Nkubu town, where data was collected by use of structured questionnaires.  size was 19 community pharmacies and 380 households. Descriptive statistics were used for data analysis. Results are presented in tables. Results: The study showed that 23.9% (n=91) of the households use pit latrines while 73.5% (n=14) of the community pharmacies use burning as the common methods of pharmaceutical waste disposal. Conclusion: The common method of pharmaceutical waste disposal being practiced in community pharmacies was burning while for households was emptying in the pit latrine. Disposal of unwanted pharmaceutical products through unsafe methods along the sanitation chain was prevalent among the respondents. Recommendation: There is need to create public awareness and establish educational programs regarding management and handling of unwanted pharmaceutical wastes among community pharmacies and households in Nkubu town.
Keywords: community pharmacies; household, pharmaceutical waste; pharmaceutical waste management; Sanitation; sanitation value chain